Fisheries Conservation and Marine Protected Area Establishment in Indonesia - Davina Oktivana (Padjadjaran Journal of International Law, 2023)
Marine protected areas (MPAs) aim to protect marine ecosystems or habitats within ecologically meaningful boundaries. MPAs are based on the combination of the conservation of marine living resources and the protection of marine habitats or ecosystems. The objective of MPA is to balance diverse societal objectives by taking into account the knowledge and uncertainties about biotic, abiotic, and human components of ecosystems and their interactions and applying an integrated approach to fisheries within eco-relevant boundaries in an integrated manner. The traditional approach provided in 1982 LOCS (zonal management approach and species-based approach) needs to be revised to be implemented under the MPA concept to achieve MPA objectives. In comparison, the ecosystem-based and precautionary approaches are ideally suited to be applied with MPA conception. The most prominent feature of the precautionary approach is scientific evidence, which is essential for establishing a protected area. This paper is a review of Indonesia's implementation to achieve sustainable fisheries, particularly the environmental aspect. Particular attention must be given to the fact that there is no correlation between Indonesian MPAs and IFMAs. The RPJMN focuses on capture fish that take into account the MSY value and eliminate the constraints by strengthening management and institutionalization of IFMAs, optimizing fishery productivity, and harmonizing marine spatial planning, particularly in the coastal areas and small islands. This paper also discusses the impact of Indonesian maritime zones on the environment and marine areas. The results of the report show that Indonesian marine zones are vulnerable to IUUF, especially in the Natuna Sea, and the enforcement of the Indonesian laws and regulations focused on the IUFF could be better, but it can also be used to protect the violation in conservation areas. MMAF Regulation 22/2021 can be considered as one aspect required in EAFM to provide scientific evidence (TAC and MSY level) that enables sustainable development in fisheries.